2013
DOI: 10.1042/bst20130234
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial trafficking in neurons and the role of the Miro family of GTPase proteins

Abstract: Correct mitochondrial dynamics are essential to neuronal function. These dynamics include mitochondrial trafficking and quality-control systems that maintain a precisely distributed and healthy mitochondrial network, so that local energy demands or Ca2+-buffering requirements within the intricate architecture of the neuron can be met. Mitochondria make use of molecular machinery that couples these organelles to microtubule-based transport via kinesin and dynein motors, facilitating the required long-range move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 80 publications
1
98
0
3
Order By: Relevance
“…Neurons are especially sensitive to perturbations in mitochondrial transport given the length and complexity of their axons and dendrites. As such, aberrant mitochondrial transport results in deficits in ATP production, which is important for neurotransmitter synthesis, vesicular recycling and maintenance of the membrane potential (Birsa et al, 2013;Brodin et al, 1999;Saxton and Hollenbeck, 2012). Mitochondrial transport along microtubules is a Ca 2+ -sensitive process; here, the mitochondrial adaptor proteins of the Miro family serve as Ca 2+ sensors that regulate the interaction of mitochondria with members of the trafficking kinesin protein (TRAK)/Milton family of motor adaptors and the motor protein kinesin-1 (Tang, 2015;Lee and Lu, 2014;Lin and Sheng, 2015;Sheng, 2014).…”
Section: Mitochondrial Transport and Bioenergeticsmentioning
confidence: 99%
“…Neurons are especially sensitive to perturbations in mitochondrial transport given the length and complexity of their axons and dendrites. As such, aberrant mitochondrial transport results in deficits in ATP production, which is important for neurotransmitter synthesis, vesicular recycling and maintenance of the membrane potential (Birsa et al, 2013;Brodin et al, 1999;Saxton and Hollenbeck, 2012). Mitochondrial transport along microtubules is a Ca 2+ -sensitive process; here, the mitochondrial adaptor proteins of the Miro family serve as Ca 2+ sensors that regulate the interaction of mitochondria with members of the trafficking kinesin protein (TRAK)/Milton family of motor adaptors and the motor protein kinesin-1 (Tang, 2015;Lee and Lu, 2014;Lin and Sheng, 2015;Sheng, 2014).…”
Section: Mitochondrial Transport and Bioenergeticsmentioning
confidence: 99%
“…Subcellular fractionation experiments suggested that this protein localizes at least in mitochondria. Although the precise function of TPPP in mitochondria is completely unknown to date, it may be possible that TPPP plays a role as a mitochondrial motor protein, considering its binding capacity to tubulin [40]. Similar to other mitochondrial membrane proteins such as MFN1, MFN2 or DRP1 [29,41], TPPP demonstrates GTPase activity in the presence of zinc [9] and magnesium [21] ions, suggesting its multiple roles in physiological dynamics (for example, signal transduction).…”
Section: Discussionmentioning
confidence: 99%
“…Det er kjent at Ca ++ -nivået spiller en viktig rolle i de dynamiske forholdene innad i aksonet (20,22). Svikt i Na + /K + -ATPaseaktivitet som følge av demyelinisering og økt Na + -konsentrasjon intraaksonalt kan videre reversere Na + /Ca ++ -pumpen og medføre opphopning av intraaksonalt Ca ++ (23).…”
Section: Gir Demyelinisering Mitokondrieforandringer?unclassified